The The Influence of Role Play Method by Hand Puppet Media in Speaking Class of Santo Rafael Kindergarten’s Students - Putu Windi Ridayanti; Kadek Devy Marleni; Ni Nyoman Ari Ratnadi (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2021)
play gave a significant effect to the students’ speaking competency. Hand puppetsare dolls that are used as media or tools used in learning activities. Types of puppets thatare usually used are hand puppets made of pieces of cloth. Methods: The research designused a pre-experimental design with a one group pre-posttest design. The populationsused in this study were children in B group class in Santo Rafael Singaraja. The speakingmeasurement used an observation sheet in which it guided by a task. The sample sizeused is 30 respondents who have been selected using a total sampling technique. Thisstudy used parametric statistics using Paired Sample T-test with a significant level of α =0.05. Results: The results showed that the pre-test mean was 56.00, and the post-test meanwas 68.33. The results of parametric statistical tests using the Paired Sample T-testshowed pre and post results (0.000) <α (0.05), which means that H0 is rejected and Ha isaccepted. Conclusion: This shows that there is an influence of the role-play method byhand puppet media in speaking class of Santo Rafael Kindergarten Students.